Prediction of Small Bowel Obstruction Caused by Bezoars Using Risk Factor Categories on Multidetector Computed Tomographic Findings. (15th June 2016) - Kuang, Lian-qin; Zhao, Da-wei; Cheng, Cheng; Wang, Yi
Abstract : Objectives . The aim of this study was to detect factors associated with small bowel obstruction (SBO) caused by bezoars on multidetector computed tomographic findings. Methods . We retrospectively reviewed 61 patients who had bezoars in the small bowels on MDCT. The patients were divided into SBO patients group and non-SBO patients group. The mean values of the diameter, volume, and CT attenuation as well as location and characteristics of the bezoars were compared between the two groups. Multivariate analysis was performed to determine factors associated with SBO. Results . There were 32 patients (52.5%) in the SBO group and 29 patients (47.5%) in the non-SBO group. The bezoars in the SBO group had greater values of each mean diameter and mean volume than those in the non-SBO group (3.2 ± 0.5  cm versus 1 . 6 ± 0 . 7  cm, P < 0.0001, 14.9 ± 6 . 4  cm 3 versus 2.5 ± 2.7  cm 3, P < 0.0 0 01, resp.) and had a lower CT attenuation than the non-SBO group (55.5 ± 23.4 versus 173.0 ± 68.0, P < 0.0 0 01 ). The SBO group had higher prevalence of phytobezoar appearance (75.0% versus 10.3%, P < 0.0001 ). Major diameters of bezoar and phytobezoar were significant independent risk factors associated with SBO (odds ratio = 36.09, 8.26, resp., and P = 0.0004, 0.044, resp.). Conclusions . Major diameter of bezoar or phytobezoar is a potential risk factor associated with SBO.